Mısır’da Osmanlı Hayranı Bir Entelektüel: Ahmet Şevki ve Fikirleri / An Ottoman Admirer Intellectual in Egypt: Ahmed Shawqi And His Ideas - Kırmızı, İsmail; Tekin, Zeki (Journal of History Culture and Art Research, 2013)
Öz Mısır, doğu-batı güzergâhının en önemli bölgesi olan Akdeniz havzasının batıya açılan kapısı konumunda olmasından her devirde büyük devletlerin dikkatlerini üzerine çekmiş ve ilgi odağı olmuştur. Mısır’ın stratejik önemi, 19. yüzyıla geldiğimizde Fransa ve İngiltere’nin bu ülkeye yönelik sömürge faaliyetlerinin nedenini oluşturmuştur. Gerek Avrupa devletlerinin Mısır’daki sömürge faaliyetleri, gerekse Mısır’ın Osmanlı Devleti’ne olan uzaklığı bu ülkede çeşitli fikir akımlarının oluşmasına da katkı sağlamıştır. Özellikle Mısır aydınlarının Osmanlı hilafetine bakışı ve farklı milliyetçilik anlayışlarının ortaya çıkması bunlardan birkaçını oluşturmuştur. Mısır ve bu ülkede yaşayan entelektüeller üzerinde İslamcılık ve milliyetçiliğin etkisi derinden hissedilmekte idi. Mısır’daki entelektüellerden Ahmet Şevki’yi seçmemizin nedeni, onun Türk asıllı Arap olması ve yaşadığı dönemde II. Abdülhamit’e ve Osmanlı hilafetine olan bağlılığı idi. Bu dönemde Mısır’da milliyetçilik kavramı birkaç farklı şekilde algılanıyordu. Ahmet Şevki’nin milliyetçilik anlayışı Osmanlı Hilafetine Bağlı Mısır Milliyetçiliği idi. Hilafete bağlı olduğundan İslam Birliği düşüncesine sahip; Mısır’a olan sevgisi yönüyle de milliyetçi bir entelektüel olan Ahmet Şevki’nin İslam birliği düşüncesi ve milliyetçi yönü bu çalışmanın ana konusunu oluşturmaktadır. Abstract Egypt is in the position of the gateway of the Mediterranean basin to the West which is the most significant region of eastern-western route. Therefore, it has attracted the attention of big countries and has been a center of interest every era. The strategic importance of Egypt in 19th century always drew the high attention of France and Great Britain to exploit the area. Moreover; Egypt could not be totally attached to the Ottoman Empire because of the distance to the Sublime Porte. Both the distance to the Sublime Porte and the exploitation activities of European countries led to bring about different movement of thought in Egypt. Especially, the idea of Egyptian intellectuals to the Ottoman Empire and different nationalism approaches are some of these different movement of thought in Egypt. The effects of Islamism and Nationalism have been felt deeply especially by the intellectuals living in Egypt. The reason why Ahmad Shawqi was chosen among these intellectuals is that he was originally Turkish and was deeply attached to Abdulhamit II and to the caliphate during his life-time. The nationalism idea was being recognized in some different ways in Egypt at that time. The nationalism idea of Ahmad Shawqi was based on the Egyptian Nationalism attached to the Ottoman Caliphate. Ahmad Shawqi’s Union of Islam and Nationalism idea is the core of this study. Shawqi has got the Union of Islam idea since he was attached to the caliphate and is a nationalist intellectual because of his compassion to Egypt.